Digital Transformation in Human Resource and Operational Management of Snake Fruit Plantations - Kadek Dimas Ganes Grahista; Sulistyo Dwi Sancoko (Komunitas Dosen Indonesia, 2025)
Digital transformation is crucial for modernizing the agricultural sector, improving operational efficiency, record accuracy, and resource management transparency. This study aims to design and develop an integrated information system using both web and mobile platforms to address managerial challenges at I Nyoman Suryadiputra Garden, specifically related to the manual record-keeping of harvest data and employee attendance, as well as the lack of a monitoring system that hinders worker discipline and causes operational inefficiencies. The research is conducted in three phases: first, the initial phase with manual management and disorganized records, second, the development of the digital system, and third, the implementation phase, where digital records enhance efficiency and transparency. Unlike existing digital frameworks in sectors such as oil palm or livestock farming, this system provides a comprehensive solution by integrating harvest records, employee attendance, payroll, monthly reports, monthly performance report, guidelines & procedures, and leave requests into a single platform, support the implementation of the initial steps of Agriculture 4.0. Key features include digital attendance via QR codes, activity reporting, harvest record-keeping, and leave requests, all stored in a centralized MySQL database. Flutter, React, and Laravel were selected due to their scalability and efficiency in handling large datasets. Flutter enables efficient cross-platform mobile development, React offers a dynamic web interface, and Laravel provides an optimal backend framework for large-scale data management. Preliminary analysis predicts a 30% reduction in time spent on attendance tracking, a 40% reduction in harvest data errors, and a 50% reduction in employee absenteeism, indicating enhanced worker discipline. This research follows a design science methodology, employing iterative design, testing, and refinement. The developed system is adaptable to other agribusiness sectors.